EXPLORING YORUBA FIRE CULTURES THROUGH PROVERBS - Asiyanbi, Adeniyi (Proverbium - Yearbook, 2023)
This article argues that Yoruba proverbs are an essential source of popular wisdom on socio-environmental practices accessible through creative reconstruction and interpretation of their historical contexts. Learning from the everyday knowledge and accumulated wisdom of ordinary people holds significant promise at a time of unprecedented socio-environmental crisis and widespread calls for transformative change across scales. Drawing on the collection of Yoruba proverbs by Oyekan Owomoyela, broader Yoruba oral literature, Yoruba popular culture and a cross-disciplinary selection of academic literature, this article curates and reimagines nine Yoruba proverbs on the theme of fire, using these as an entry point to interrogate aspects of ecology and local understanding and practices of living with fires among the Yoruba people.